1997
DOI: 10.1897/1551-5028(1997)016<1417:gddeir>2.3.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Glutathione-Dependent Detoxifying Enzymes in Rainbow Trout Liver: Search for Specific Biochemical Markers of Chemical Stress

Abstract: Abstract-Activities of trout liver microsomal glutathione S-transferase (GST) and a series of cytosolic glutathione-dependent detoxifying enzymes were determined after a single intraperitoneal treatment with phenobarbital, 2,2-bis (p-chlorophenyl)-1,1-dichloroethane (p,pЈ-DDE), 2,3,-dimethoxynaphthoquinone (NQ), or 2, 3,7,. This study aimed to find xenobiotic-specific parameters applicable as biochemical markers of the impacts of the prototypal xenobiotics. The effects of xenobiotics on cytosolic GST activitie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
22
1

Year Published

1997
1997
2015
2015

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 47 publications
(25 citation statements)
references
References 26 publications
2
22
1
Order By: Relevance
“…Decreased GR activity may lead to GSH depletion if the depletion cannot be corrected by the synthesis of new glutathione molecules. Hepatic GR was increased in rainbow trout after a short-term exposure to Phenobarbital, p,p 0 -dichlorodiphenyldichloroethylene (DDE), or the prototypal oxidation -reduction cycling compound 2,3-dimethoxynaphthoquinone (Petřivalský et al, 1997). The mechanism of regulation of GR in organism is still unclear, and the increase in its activity can be interpreted as an adaptive response to oxidative stress.…”
Section: Discussionmentioning
confidence: 99%
“…Decreased GR activity may lead to GSH depletion if the depletion cannot be corrected by the synthesis of new glutathione molecules. Hepatic GR was increased in rainbow trout after a short-term exposure to Phenobarbital, p,p 0 -dichlorodiphenyldichloroethylene (DDE), or the prototypal oxidation -reduction cycling compound 2,3-dimethoxynaphthoquinone (Petřivalský et al, 1997). The mechanism of regulation of GR in organism is still unclear, and the increase in its activity can be interpreted as an adaptive response to oxidative stress.…”
Section: Discussionmentioning
confidence: 99%
“…Considering its importance in defense against toxic effects of xenobiotics, GR has received much attention in biomonitoring studies. In one study, hepatic GR was increased in rainbow trout after a short-term exposure to Phenobarbital, p,p′-dichlorodiphenyldichloroethylene (DDE), or the prototypal oxidation-reduction cycling compound 2,3-dimethoxynaphthoquinone (Petrivalsky et al, 1997). The mechanism of regulation of GR in Daphnia magna is still unclear, and the increase in its activity can be interpreted as an adaptive response to oxidative stress.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, although reduced glutathione peroxidase (25,30) and glutathione reductase (25) activities were found in fish exposed to environmental pollution, both enzymes in general showed induced activities in the liver (7,28,31). These Acute and subchronic exposure to pollutants seems to increase reduced glutathione contents in fish cells (26,(32)(33)(34) while fish submitted to heavy and extensive chronic exposure seem to be unable to maintain high constitutive glutathione and total glutathione levels (11,28; Wilhelm Filho D, Torres MA, Testa CP and Tribess TB, unpublished results; present study). The decrease observed both in reduced and oxidized glutathione concentrations may be attributable to the decrease in total glutathione.…”
Section: Effect Of Pollutionmentioning
confidence: 99%
“…Although some studies have shown induction of SOD (27,28) and other antioxidants (27) or biotransformation enzymes (27,28,31) under pollution exposure, unaltered or lowered SOD activities have been also found in other fish species (7,32). GST, together with EROD activity, is usually enhanced after exposure to different types of organic pollutants, both in laboratory studies (e.g., 31,34) and in field studies (27,31). They represent a complex system related to xenobiotic biotransformation (phase I) and conjugation and excretion (phase II), consisting of prospective biochemical markers of environmental contamination by organic compounds such as polycyclic aromatic hydrocarbons and polychlorinated biphenyls (36).…”
Section: Effect Of Pollutionmentioning
confidence: 99%